2014
DOI: 10.1038/ismej.2014.240
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomics of N2-fixing cyanobacteria in the Amazon River plume

Abstract: Biological N 2 fixation is an important nitrogen source for surface ocean microbial communities. However, nearly all information on the diversity and gene expression of organisms responsible for oceanic N 2 fixation in the environment has come from targeted approaches that assay only a small number of genes and organisms. Using genomes of diazotrophic cyanobacteria to extract reads from extensive meta-genomic and -transcriptomic libraries, we examined diazotroph diversity and gene expression from the Amazon Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 57 publications
3
21
0
Order By: Relevance
“…Although it is widely accepted that Trichodesmium has increased abundance in the western North Atlantic relative to other regions (Luo et al ., ), an important consideration is that these Atlantic datasets typically include high station‐to‐station variability of up to three orders of magnitude (Foster et al ., ; Rouco et al ., ). This variability in Trichodesmium abundance may, in part, be driven by freshwater input from the Amazon River plume for studies that transect this feature (Foster et al ., ; Subramaniam et al ., ; Rouco et al ., ; Hilton et al ., ). Rouco et al .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Although it is widely accepted that Trichodesmium has increased abundance in the western North Atlantic relative to other regions (Luo et al ., ), an important consideration is that these Atlantic datasets typically include high station‐to‐station variability of up to three orders of magnitude (Foster et al ., ; Rouco et al ., ). This variability in Trichodesmium abundance may, in part, be driven by freshwater input from the Amazon River plume for studies that transect this feature (Foster et al ., ; Subramaniam et al ., ; Rouco et al ., ; Hilton et al ., ). Rouco et al .…”
Section: Resultssupporting
confidence: 89%
“…It is possible that different Trichodesmium species, or strains, in each ocean basin have different temperature optima, and this could be resolved with qPCR primers designed to distinguish Trichodesmium at the species level. Recent studies have revealed unique features in the Trichodesmium genome (Pfreundt et al ., ; Hilton et al ., ; Walworth et al ., ) which suggest that species within this genus might have the potential for rapid evolution and adaptation in response to changing biogeochemical regimes, and this might explain differential patterns in clade abundance relative to temperature between these ocean basins. The relationship between clade abundance and temperature also may influence the potential selection and distribution of Trichodesmium clades with future ocean warming.…”
Section: Resultsmentioning
confidence: 99%
“…Reads were mapped using RNA-Seq by Expectation Maximization (RSEM) [57] with Bowtie2 [58] using default parameters. These low mapping rates were similar to other Trichodesmium field studies [59,60], and likely reflect the presence of reads of heterotrophic bacterial epibionts, which are present at high concentrations in the colonies [35,36], as well as the potential variability between the genomes of cultured Trichodesmium and field populations [59], as field populations encompass a diversity of Trichodesmium species [15,16]. To target a Trichodesmium community more representative of the field, reads were mapped to Trichodesmium-identified genes from a custom Trichodesmium metagenome database assembled by Frischkorn et al [34].…”
Section: Read Mappingsupporting
confidence: 90%
“…When relative transcript abundance of the 89 biogeochemicallyrelevant genes was compared across the river and plume stations, river samples were more strongly dominated by amoA, nirK and amtB transcripts generated by Thaumarchaeota populations (Figure 7). Nitrogen fixation transcripts were a more important feature of the plume transcriptomes, particularly at two stations where diatoms harbored an endosymbiotic Nfixing cyanobacterium (Hilton et al, 2014;Satinsky et al, 2017). Transcripts from the high-affinity phosphate transporter (pstACS) were more important at the plume sites and the TAP station, while the low-affinity phosphate transporter (pitA) was more important at the other river stations and the coastal plume stations, consistent with generally higher PO 4 availability in the river compared to the tributaries and ocean.…”
Section: Discussionmentioning
confidence: 99%